PENGARUH LAYANAN KONSELING KELOMPOK TEKNIK SELF MANAGEMENT UNTUK MEREDUKSI PERILAKU KECANDUAN SMARTPHONE SISWA KELAS VIII A SMP NEGERI 10 KOTA BENGKULU - Yanda Dipa Subawa; Yessy Elita; Afifatus Sholihah (Consilia : Jurnal Ilmiah Bimbingan dan Konseling, 2023)
This research is motivated by the high number of smartphone addicts among students at SMP Negeri 10 Bengkulu City. The purpose of this study was to determine the effect of group counseling services using self-management techniques to reduce smartphone addiction behavior in students. The population of this study was 29 students. The sample used a purposive sampling technique so that six students were sampled and used a Likert scale model questionnaire as a data collection technique. The data analysis technique used the t-test (paired sample t-test) which showed a value of t = 15,452 and sig (2-tailed) 0.000 <0.05 so that Ha was accepted. This means that there is a significant influence of group counseling services with self-management techniques to reduce students' smartphone addiction behavior.